How Screen Readers Impact the Academic Works of College and Graduate Students with Visual Impairments - Sevgi Kırboyun Tipi (Sakarya University Journal of Education)
This study explored the effectiveness of screen readers on the academic life of higher education students with visual impairments, including reading, writing, access to the internet, exams, and general information for their courses. This study was designed as a qualitative study and applied a phenomenological approach in order to discuss the experiences of higher education students who use screen readers as assistive technology. One college student and six graduate students with visual impairments were interviewed in the United States. The findings revealed that higher education students with visual impairments benefitted from screen readers; however, they also noted some limitations: difficulties in accessing printed classroom materials, inaccessible digital content, and time lost due to technical issues. Students with visual impairments should be offered accessible documents such as electronic versions of classroom materials, accessible PDFs and websites, and software compatible with JAWS. Universities should provide accessibility training for lecturers who want to better serve students with visual impairments. University information technology services need to train their technical services staff about screen readers to provide 24/7 professional services for students with visual impairments.